Removal of Well-Fixed Tibial Cone in Revision Total Knee Arthroplasty—A Uniquely Challenging Yet Necessary Scenario - Scully, William F.; Deren, Matthew E.; Sultan, Assem A.; Samuel, Linsen T.; Nageotte, William; Molloy, Robert M.; Krebs, Viktor E. (The Journal of Knee Surgery, 2019)
The number of revision total knee arthroplasties (TKA) performed in the United States continues to increase. While advancements in implant design and surgical technique have led to improved outcomes compared with historical data, these cases remain technically demanding with high rates of aseptic failure and worse patient reported outcome scores compared with primary total knee arthroplasty. One particular problem commonly encountered in revision knee arthroplasty is bone loss, particularly in the epiphyseal region, which negatively impacts the structural integrity of the implants. Various modular metaphyseal sleeves and cones in conjunction with stemmed implants have been designed to enhance metaphyseal fixation, corroborated by multiple studies demonstrating excellent midterm results involving cones, and sleeves. Commercially available revision systems that incorporate metaphyseal cones are currently widely utilized in revision TKA. For tibial defects, both symmetric and asymmetric cone options are available. Excellent midterm results have been reported with use of this device in the setting of severe proximal tibial bone loss in revision TKA surgery. With the enhanced fixation provided by various sleeve and cone augments, implant removal in the setting of recurrent infection or implant failure can be extremely challenging. Consequently, in this work, we sought to describe an algorithmic approach for removing a tibial cone in conjunction with the overlying tibial baseplate. A review of the literature has also been conducted for complex surgical techniques regarding removal of well-fixed implants in revision total knee arthroplasty.
Keywords: metaphyseal tibial cone removal; well-fixed; revision total knee arthroplasty; review; complex removal; osteotome stacking